Penilaian Penerapan Corporate Governance Menggunakan Model Peratingan CGCG UGM - Mentari Dwi Aristi; Supriyadi Supriyadi (COSTING : Journal of Economic, Business and Accounting, 2019)
The existence of regulations that require the application of GCG and the many benefits that the company has obtained has a good effect. This study aims to assess the quality of corporate governance implementation at PT Bumi Siak Pusako (PT BSP) using CGCG UGM rating model. The CGCG UGM rating model consists of 497 questions which are based on four basic constructs, namely transparency, accountability, responsibility, and fairness. This research uses a research method with a case study approach. Data were collected using questionnaires from the CGCG UGM rating model, interviews, and documentation. The analytical technique used is the analysis technique of CGCG UGM rating model that is divided into 3 stages, namely the determination of scores, calculations of scores, and rating categories. The result of the assessment of corporate governance implementation at PT BSP using CGCG UGM rating model shows that PT BSP is ranked A ++ with a total score of 3748 from a maximum value of 4155, or 90%. The A ++ is second rank in the 16 ranks provided by CGCG UGM, it shows that PT BSP has not been optimal in implementing corporate governance in terms of adopting, implementing, and developing voluntary regulations. Keyword: Corporate Governance, Peratingan Model, CGCG UGM